P107: Two-years long genetic screening of breast cancer patients in Novosibirsk (Russia) – first practical results. Issue 1 (November 2015) - Kovalenko, S.; Paul, G.; Matyash, N.; Kozyakov, A.
Abstract : Mutations in BRCA1 and CHEK2 genes associated with hereditary breast cancer were tested in 7920 randomly selected individuals of Novosibirsk (Russia). Mutations BRCA1 5382insC and CHEK2 1100delC were the most frequent, they were found in 0.25% and 0.4% of the general population respectively. We suggested to find mutations carriers by the screening of all breast/ovary cancer patients for the most frequent mutations (BRCA1 5382insC and CHEK2 1100delC) with subsequent analysis of the first-line relatives of cancer patients if one of the mutations was found. From June 2013 till January 2015, all patients from Novosibirsk regional oncology hospital with the diagnosis of breast cancer and some patients with the diagnosis of ovary cancer were tested for mutations BRCA1 5382insC and CHEK2 1100delC. A total of 2655 cancer patients were analyzed independently of their family history. We found 122 mutations carriers, among them 99 patients with mutations in BRCA1 gene and 23 patients with mutation CHEK2 1100delC. Among mutation carriers, 105 patients agreed to have a medical genetic counseling and after pedigree analysis 193 first-line relatives aged above 25 years were elucidated. One hundred ten first-line relatives of mutation carriers were analyzed for the mutations presence and 40 mutations carriers were found among relatives. From September 2013 till December 2013, 32 relatives of BRCA mutation carriers underwent breast MRI. In 5 cases, breast cancer was detected by MRI and all cancers except one were confirmed histologically with biopsy analysis. Importantly, all tumors were 5 mm and less in size, stage I cancer was detected in all cases. At a follow-up of 1.5 years, all 105 mutation carrier probands were interviewed by phone regarding possible relapse and/or possible primary cancer in their relatives. Five of 105 probands lost to follow-up may have died. Among responding 100 patients, 2 died as reported by relatives, relapse was reported in 7 probands – mutation carrier probands, primary tumors were reported in 8 relatives of probands. Mutation carrier probands reported one bilateral breast cancer, four ovary cancers, one bladder cancer and one non-specified oncogynecological tumor. There were five cases of primary breast cancer, one ovary cancer, one colon cancer, one lung cancer among relatives of breast cancer patients with mutations. The frequency of tumors found in mutation carriers exceeded the average frequencies of cancer for this population. The economic value of the regional genetic screening can be easily estimated according to the data obtained in this study and data on treatment cost for stage I and stage IV breast cancer. To summarize briefly, the screening of hot-spot mutations provides not only increase of lifespan expectancy and life quality for mutation carriers, but can be also a tool for financial saving of medical system due to the increase of early stage breast cancer detection.